The Role of Company Initiated Learning Program on Employees’ Learning about Sustainability in Organization - Razali, Murni Zarina Mohamed; Jamil, Rossilah (Journal of Entrepreneurship, Business and Economics, 2022)
Many organizations have embedded sustainability strategy in the organization nowadays. Sustainability strategy drive the organization to set an action that focusing on balancing their commitment between planet, people and profit.  In the effort to implement the strategy, employees in the organization must possess sufficient knowledge and skills related to sustainability practices. The process of acquiring knowledge about sustainability or sustainability learning (SL) is critical in embedding sustainability in organizations. Due to the urgently needs, this paper aims to determine how does company-initiated learning program facilitate SL among employees in the organization. In exploring the role of the company-initiated learning program in facilitating employees in organization to learn about sustainability, this paper also presents the program offered for SL, the benefits of the program and employees’ preferred learning program approach to learning sustainability. Based on this study, company-initiated training program is highly important in ensuring sustainable learning happens successfully. In this study context, company-initiated learning programs that emphasizes on informal learning, such as the Sustainability event (Corporate Social Responsibility Event) is effective more than formal learning program in supporting employees to learn about sustainability. The finding of this study is significant for the organization in developing learning program about sustainability to employees. Research paper Keywords: Sustainability, Sustainability learning, Formal learning, Informal learning, Training, Knowledge Reference to this paper should be made as follows: Razali, M. Z. M., & Jamil, R. (2022). The Role of Company Initiated Learning Program on Employees’ Learning about Sustainability in Organization. Journal of Entrepreneurship, Business and Economics , 10 (2), 192–209.